Oral health status and quality of life of the parental caregivers of children with Down syndrome: A case-control study. (March 2023) - Schwertner, Carolina; Silva, Caroline Dias da; Grando, Débora; Hilgert, Juliana Balbinot; Hashizume, Lina Naomi
The aim of this study was to investigate the oral health status and quality of life (QOL) of the parental caregivers of individuals with Down syndrome (DS), and to evaluate whether there is an association between these variables. The sample of this cross-sectional study was composed by parental caregivers of children with DS (CCDS) and parental caregivers of children without DS (CNDSC). Oral examination was undertaken and a questionnaire was given to participants. QOL was evaluated by WHOQOL-Bref. CCDS presented a higher number of dental prosthesis users and higher gingival bleeding index compared to CNDSC. When oral health was associated with QOL, the use of dental prosthesis was associated with physical domain and the variables having chronic disease and family income were associated with the social domain for both caregivers. The results suggest that caregivers of children with DS have similar oral health and QOL compared to caregivers of children without DS. In both caregivers, oral health status is associated with QOL.